Mesenteric fibromatosis involving intestine mimicking a gastrointestinal stromal tumor - Parmar, Sakshi J.; Kamat, Manmohan M.; Mishra, Avani; Setipalli, Saisree (International Surgery Journal, 2023)
Mesenteric fibromatosis (MF) or intra-abdominal desmoid tumour is a rare proliferative disease affecting the mesentery. MF is a locally aggressive tumour that lacks metastatic potential, but the local recurrence is common. We report a case of 33-year-old female with chief complaints of mass in abdomen which was hard on palpation arising from the pelvis and extending up to the umbilicus. Magnetic resonance imaging (MRI) suggestive of soft tissue mass and exploration was planned. Intra-operatively a mass of 16×16×8 cm with attached ileum and caecum which was excised completely and sent for histopathological examination. Histopathology was suggestive of Mesenteric fibromatosis spindle cell type. Considering the rarity of this tumour and difficulties in diagnostic and therapeutic ambit, we believe it is justified to publish this case which came to our observation.